2018
DOI: 10.1159/000487054
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator as an Antiangiogenic Agent in Experimental Corneal Neovascularization in Rabbits

Abstract: Aims: Anti-vascular endothelial growth factor agents effectively treat age-related macular degeneration and myopic choroidal neovascularization (CNV). Tissue plasminogen activator (tPA), a fibrinolytic compound, is used as an adjuvant to displace submacular hemorrhage and to treat type 2 CNV. The purpose of this study was to investigate in in vitro and in vivo experiments the antiangiogenic impact of tPA itself. Methods: The impact of tPA on the proliferation of human umbilical vein endothelial cells (HUVECs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Grafts are particularly sensitive to ischemia as angiogenesis occurs the first week after surgery [12][13]. The fibrinolytic effects of tPA have altered neovascularization in animal models and as a result, it is possible a large dose, such as that in our patient, could compromise both microvascular replant and graft survival [14][15].…”
Section: Discussionmentioning
confidence: 97%
“…Grafts are particularly sensitive to ischemia as angiogenesis occurs the first week after surgery [12][13]. The fibrinolytic effects of tPA have altered neovascularization in animal models and as a result, it is possible a large dose, such as that in our patient, could compromise both microvascular replant and graft survival [14][15].…”
Section: Discussionmentioning
confidence: 97%
“…We have focused on the role of tPA in angiogenesis and have examined its effects on angiogenesis in vivo and in vitro studies. Arai et al [35] reported that while tPA has no direct impact on the vascular endothelial cells in vitro, tPA significantly reduced corneal neovascularization in a rabbit model. These results suggest that among the essential steps in angiogenesis, fibrin may play a pivotal role as a scaffold in the loose intercellular spaces around highly permeable vessels and that tPA may have an inhibitory effect on angiogenesis through its fibrinolytic and constrictive effects on the developing fibrovascular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that fibrin deposition during the process of angiogenesis constitutes a scaffold used by EC to form new vessels. The authors claimed that exogenous tPA can inhibit the formation of the fibrin scaffold and block the formation of new vessels and suggested that intravitreal injection of tPA might prevent retinal angiogenesis [ 40 ]. In a retinal neovascularization model, a small peptide generated from kringle 2 domain (His 65 - Tyr 76 ) of tPA attained antiangiogenic effects on EC in vitro and in vivo.…”
Section: Plasminogen Activator–plasmin Systemmentioning
confidence: 99%